2019
DOI: 10.1002/cbin.11067
|View full text |Cite
|
Sign up to set email alerts
|

Human bone marrow‐derived MSCs spontaneously express specific Schwann cell markers

Abstract: In peripheral nerve injuries, Schwann cells (SC) play pivotal roles in regenerating damaged nerve. However, the use of SC in clinical cell‐based therapy is hampered due to its limited availability. In this study, we aim to evaluate the effectiveness of using an established induction protocol for human bone marrow derived‐MSC (hBM‐MSCs) transdifferentiation into a SC lineage. A relatively homogenous culture of hBM‐MSCs was first established after serial passaging (P3), with profiles conforming to the minimal cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 127 publications
0
11
0
Order By: Relevance
“…Accumulating evidences have indicated that tumour cells differentiating towards Schwann‐like cell could accelerate the predisposition for PNI of tumours. 19 , 37 , 38 , 39 In this study, the level of S100A4, p75NTR and GFAP, which had been characterized as Schwann cell markers, 11 , 12 was evidently increased at nerve invasion frontier. And the relevancy analysis indicated that CXCR4 expression level was positively correlated with S100A4, p75NTR and GFAP level at nerve invasion front.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Accumulating evidences have indicated that tumour cells differentiating towards Schwann‐like cell could accelerate the predisposition for PNI of tumours. 19 , 37 , 38 , 39 In this study, the level of S100A4, p75NTR and GFAP, which had been characterized as Schwann cell markers, 11 , 12 was evidently increased at nerve invasion frontier. And the relevancy analysis indicated that CXCR4 expression level was positively correlated with S100A4, p75NTR and GFAP level at nerve invasion front.…”
Section: Discussionmentioning
confidence: 54%
“…Schwann cells are fundamental to the merisis and luxuriance of nerves and conducive to the guidance of axons. 11 , 12 A growing body of evidence showed that the level of Schwann cell hallmarks, including glial fibrillary acidic protein (GFAP), p75 neurotrophin receptor (p75NTR), S100 calcium‐binding protein A4 (S100A4), was significantly increased in many tumour with PNI, including melanoma, 13 breast cancer, 14 prostate cancer, 15 colorectal cancer. 16 Hence, researchers inferred that the differentiation of cancer cell towards Schwann‐like cell might be responsible for the PNI occurrence of tumours.…”
Section: Introductionmentioning
confidence: 99%
“…Schwann cells, which constituted the main cells of peripheral nerve, are essential for peripheral nerve survival and development and related to the maintenance of axons. Studies showed that the expression of Schwann cell biomarkers, including S100 calcium binding protein A4 (S100A4), p75 neurotrophin receptor (p75NTR), and glial fibrillary acidic protein (GFAP) was involved in occurrence and metastasis of tumors through increased migration and invasion capabilities . Furthermore, a large body of evidence showed that S100A4 was evidently increased in tumors with PNI, such as melanoma, colorectal cancer, prostate cancer, breast carcinoma .…”
Section: Introductionmentioning
confidence: 99%
“…It is very true that we can hardly say or judge the differentiation efficiency of ADSCs simply via S100β. As the previous study mentioned, many Schwann cell markers (e.g., GFAP, P75NGFR, MPZ, and S100β) can be employed to characterize Schwann cell phenotype, but all of these markers had low expression (less than 15%) following the established neural induction protocol ( Ramli et al, 2019 ). The accurate characterization of Schwann cell-like differentiation may require more rigorous assessments (including but not limited to Schwann cell specific markers and transcription factors listed above).…”
Section: Discussionmentioning
confidence: 99%